2007
DOI: 10.1080/13682820701261991
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physical properties of novel S‐shaped liquid crystal oligomers

Abstract: We prepared novel S-shaped liquid crystal oligomers, the 4,49-bis (v-(2-(v-(4-(cyanophenyl)phenyloxy)alkyloxy)phenyloxy)alkyloxybiphenyls (S-n), and investigated their transition behaviour. The oligomer with even-numbered spacers (S-6) exhibited a nematic phase, whereas the oligomer with odd-numbered spacers (S-7) exhibited nematic and smectic A phases. Transition properties of the S-shaped oligomers are compared with those of the corresponding monomeric and U-shaped dimeric compounds. The entropy changes asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, we reported pronounced odd-even effects in the transition behavior of U-shaped systems [12]. Moreover, we have reported the synthesis and transition properties of S-shaped molecules in which two U-shaped mesogenic molecules are connected [13].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we reported pronounced odd-even effects in the transition behavior of U-shaped systems [12]. Moreover, we have reported the synthesis and transition properties of S-shaped molecules in which two U-shaped mesogenic molecules are connected [13].…”
Section: Introductionmentioning
confidence: 96%
“…discotic liquid crystal. 5 However, there are many other categories such as cholesterol-based liquid crystal, H-shaped, 6 S-shaped, 7 star shaped liquid crystal 8 etc. Over a short period of our research on liquid crystal we have synthesized different type of thermotropic liquid crystals and characterized their unique properties with the help of POM, DSC and powdered XRD.…”
Section: Introduciotnmentioning
confidence: 99%
“…Yoshizawa and Yamaguchi [14] have reported layered structure in the nematic phase consisting of U-shaped molecules. Recently Yoshizawa et al [15] have reported the synthesis and physical properties of novel S-shaped LC oligomers in which two U-shaped mesogenic molecules are connected. Yoshizawa et al [16] have also reported novel Y-shaped LC oligomers in which three mesogenic units are connected by 3,5-dihydroxybenzoic acid.…”
Section: Introductionmentioning
confidence: 99%